PENERAPAN MATEMATIKA PADA ILMU EKONOMI : FUNGSI KONSUMSI DAN TABUNGAN - Azahro, Ihza; Lestari , Irma Dwi; Suryandari , Novi Ayu; Lutfia, Siti; Naila Fahsya , Ghea; Sukma Raga , Dian (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study explores the relationship between consumption and savings, two interrelated economic activities that are essential to drive the economy. Consumption reflects household spending to fulfill daily needs, while savings represent the portion of income that is not spent. According to Keynes, an increase in income proportionally impacts consumption and savings. Using mathematical economics as an analytical tool, this study examines the consumption and savings functions, highlighting their direct relationship with national income. The results show that if consumption increases, savings will decrease. Because if the portion of income spent is larger, the portion set aside for savings will be smaller. If consumption decreases, savings will increase. Conversely, if the portion of income spent is smaller, the portion set aside for savings will be larger.